Gender Taboo di Media Sosial: Analisis Penerimaan terhadap ‘Perlawanan’ Danilla Riyadi di Instagram dan Youtube - Clara Ocktarida Sutisna; Nanang Krisdinanto; Brigitta Revia Sandy Fiesta (Asosiasi Pendidikan Tinggi Ilmu Komuniasi (ASPIKOM) Wilayah Riau, 2022)
This study focuses on the dynamics of women's acceptance of taboo gender issues on social media on Danilla Riyadi's Instagram and Youtube accounts. Through her social media content, Danilla is recognized as a singer whose behavior in front of the camera often triggers controversy such as smoking, drinking alcohol, showing tattoos, or saying obscene words. In the context of gender, what he does implicitly can be seen as a form of resistance to the gender taboo that confines women. This research looks at how the audience receives or perceives content with sensitive messages like this. The researcher used a qualitative approach, descriptive type, and the acceptance analysis method developed by Stuart Hall. The data was obtained through in-depth interviews with female viewers of Danilla Riyadi's account. The findings show that there are dynamics or diversity in the position of acceptance of the research subject towards Danilla Riyadi's content (dominant, negotiated, opposition). On the one hand, Danilla's content is accepted as a message that rejects gender taboo. But on the other hand, content is accepted as something that is detrimental to women, because Danilla's expression was deemed inappropriate for women.